(untitled) (GESTIÓN Y TENDENCIAS, 2025)
This exploratory work examines the use and potential of the R programming language as an advanced tool to support financial and operational auditing. Faced with the barriers and costs associated with commercial software licenses (such as SPSS, ACL, or IDEA) , R and its RStudio environment emerge as highly efficient open-source solutions for modeling large volumes of data and implementing data mining. The study demonstrates the practical application of packages such as dplyr for debugging and benford.analysis for identifying anomalous accounting transactions based on the First Digit Law (Benford’s Law). Additionally, key statistical sampling techniques are presented (MAS, systematic, stratified) , concluding that the integration of these languages is essential in the development of predictive analytical audits against fraud.